AI in Manufacturing: Driving Operational Excellence - Arvindan Badrinarayanan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the transformative impact of Artificial Intelligence (AI) in the manufacturing sector, focusing on key operational areas, including automated operations management, predictive maintenance, advanced production planning, and quality control enhancement. The article examines how AI technologies revolutionize traditional manufacturing processes through intelligent automation, data-driven maintenance strategies, sophisticated production planning, and enhanced quality control systems. The article demonstrates significant improvements in operational efficiency, maintenance optimization, production accuracy, and product quality across diverse manufacturing environments. Through detailed analysis of implementation cases and industry studies, this paper illustrates how AI integration drives operational excellence while creating new paradigms in intelligent manufacturing systems.
Keywords: AI-driven Manufacturing; Predictive Maintenance; Quality Control Enhancement; Production Planning Optimization; Industry 4.0 Transformation